Comparing an in‐person workshop and a postal Delphi survey for involving health service users in health care and health research prioritization - Lisa Ann Baumann; Anna L. Brütt (Wiley, 2023)
Abstract Introduction To involve health service users in health care and health research priority setting, different methods exist. Which method is most suitable under which circumstances is unknown. We compared a postal Delphi survey and an in‐person workshop to involve health service users in priority settings for rehabilitative care and research in Germany. Methods One hundred and eighty‐four former rehabilitants were randomly assigned to a postal Delphi survey (n = 152) or an in‐person workshop (n = 32). Two hundred and seventy‐six employees in rehabilitation were also invited to the Delphi Survey. The methodological comparison refers only to the sample of rehabilitants. Within each method, the participants agreed on the top 10 priorities for practice improvement and research in rehabilitative care. The priorities were compared descriptively. Participants' satisfaction was measured with the Public and Patient Engagement Evaluation Tool. The usability of both methods was compared based on the effort, time and material costs required for implementation. Results Seventy‐five former rehabilitants and 41 employees in rehabilitation completed both Delphi survey rounds. Eleven former rehabilitants participated in the in‐person workshop. Priorities for practice improvement showed a high degree of overlap between both methods whereas research priorities differed greatly. Participants of the in‐person workshop felt significantly better prepared, more listened to and more likely to feel that different views on the topics were discussed. Participants of the Delphi survey expressed difficulties in understanding all survey questions. The Delphi survey was more elaborate in preparation and implementation but caused lower material costs. Conclusion The differences in research priorities between the two methods could be due to the different samples, differences in the individual interests of participants or differences in the prioritization process. In‐person workshops seem to be more appropriate for complex topics, where clarifications of questions and deeper discussions are needed. Delphi surveys seem to be more suitable for easily understandable topics, larger sample sizes and when fewer financial resources are available. Patient or Public Contribution The different study phases were supported by employees in rehabilitation and former rehabilitants (e.g., developing study documents, and interpreting results).